Vulnerability of caregivers of the elderly with dementia: a cross-sectional descriptive study - Leite,Bruna Silva (2017)
ABSTRACT Objective: to evaluate the sociodemographic and clinical profile of the caregivers and its relation with the overburden from the care of the elderly with dementia. Method: a cross-sectional descriptive study; the sample was non-probabilistic, developed with caregivers of elderly people with dementia. The field of investigation was the Health Care Center of the Elderly and their Caregivers (CASIC), in the city of Niterói, Rio de Janeiro, Brazil. Data collection took place from February to June 2016, with the following instruments: a sociodemographic questionnaire and Zarit scale. Results: fifty percent of the caregivers presented moderate overburden; 38% presented little overburden; and 12% moderate/severe overburden. It was observed that the median of weekly care hours increases as the overburden increases. Caregivers with moderate to severe overburden, in the majority, do not share care. Conclusion: it is clear that the overburden of care places the caregiver in conditions of biological and psychological vulnerability.